WESTERN PERSPECTIVE ON THE FORMATION OF MADHHAB IN ISLAMIC LAW - Shaharuddin, Amir (Jurnal Syariah, 2019)
Western scholars have produced many critical studies concerning the formation of madhhab in Islamic law. They have shown interest in investigating who, when and how this uniquely Islamic institution evolved in early Muslim history. However, some of their findings appear to be contradicted with the view of the majority of Muslim scholars. For instance, instead of the eponyms they attribute Ibn Surayj (d.306/918), al-Karkhi (d.340/952) and al-Khallal (d.311/923) as the founders of the Shafi‘is, Hanafis and Hanbalis schools, accordingly. They also argue that the formation of the madhhabs was accomplished between the late 200’s/800’s and early to mid 300’s/900’s. The present article discusses these contentious issues by analysing both scholars’ arguments. It is suggested that the dispute between the scholars arises as a result of their different approaches in defining the term madhhab. While the Western scholars define madhhab as a set of collective legal rulings the Muslim scholars denote it as distinctive legal methodology.